Cysteinyl-tRNA synthetase: determination of the last E. coli aminoacyl-tRNA synthetase primary structure. - Eriani, G (1991)
The gene coding for E. coli cysteinyl-tRNA synthetase (cysS) was isolated by complementation of a strain deficient in cysteinyl-tRNA synthetase activity at high temperature (43 degrees C). Sequencing of a 2.1 kbp DNA fragment revealed an open reading frame of 1383 bp coding for a protein of 461 amino acid residues with a Mr of 52,280, a value in close agreement with that observed for the purified protein, which behaves as a monomer. The sequence of CysRS bears the canonical His-Ile- Gly -His (HIGH) and Lys-Met-Ser-Lys-Ser (KMSKS) motifs characteristic of the group of enzymes containing a Rossmann fold; furthermore, it shows striking homologies with MetRS (an homodimer of 677 residues) and to a lesser extent with Ile-, Leu-, and ValRS (monomers of 939, 860, and 951 residues respectively). With its monomeric state and smaller size, CysRS is probably more closely related to the primordial aminoacyl-tRNA synthetase from which all have diverged.